Growth hormone secretagogues prevent dysregulation of skeletal muscle calcium homeostasis in a rat model of cisplatin‐induced cachexia. Issue 3 (10th March 2017) - Conte, Elena; Camerino, Giulia Maria; Mele, Antonietta; De Bellis, Michela; Pierno, Sabata; Rana, Francesco; Fonzino, Adriano; Caloiero, Roberta; Rizzi, Laura; Bresciani, Elena; Ben Haj Salah, Khoubaib; Fehrentz, Jean‐Alain; et al.
Abstract: Background: Cachexia is a wasting condition associated with cancer types and, at the same time, is a serious and dose‐limiting side effect of cancer chemotherapy. Skeletal muscle loss is one of the main characteristics of cachexia that significantly contributes to the functional muscle impairment. Calcium‐dependent signaling pathways are believed to play an important role in skeletal muscle decline observed in cachexia, but whether intracellular calcium homeostasis is affected in this situation remains uncertain. Growth hormone secretagogues (GHS), a family of synthetic agonists of ghrelin receptor (GHS‐R1a), are being developed as a therapeutic option for cancer cachexia syndrome; however, the exact mechanism by which GHS interfere with skeletal muscle is not fully understood. Methods: By a multidisciplinary approach ranging from cytofluorometry and electrophysiology to gene expression and histology, we characterized the calcium homeostasis in fast‐twitch extensor digitorum longus (EDL) muscle of adult rats with cisplatin‐induced cachexia and established the potential beneficial effects of two GHS (hexarelin and JMV2894) at this level. Additionally, in vivo measures of grip strength and of ultrasonography recordings allowed us to evaluate the functional impact of GHS therapeutic intervention. Results: Cisplatin‐treated EDL muscle fibres were characterized by a 18% significant reduction of the muscle weight and fibre diameter together with an up‐regulation of atrogin1 / Murf‐1 genes and a down‐regulation of Pgc1‐a gene, all indexes of muscle atrophy, and by a two‐fold increase in resting intracellular calcium, [Ca 2+ ]i, compared with control rats. Moreover, the amplitude of the calcium transient induced by caffeine or depolarizing high potassium solution as well as the store‐operated calcium entry were 50% significantly reduced in cisplatin‐treated rats. Calcium homeostasis dysregulation parallels with changes of functional ex vivo (excitability and resting macroscopic conductance) and in vivo (forelimb force and muscle volume) outcomes in cachectic animals. Administration of hexarelin or JMV2894 markedly reduced the cisplatin‐induced alteration of calcium homeostasis by both common as well as drug‐specific mechanisms of action. This effect correlated with muscle function preservation as well as amelioration of various atrophic indexes, thus supporting the functional impact of GHS activity on calcium homeostasis. Conclusions: Our findings provide a direct evidence that a dysregulation of calcium homeostasis plays a key role in cisplatin‐induced model of cachexia gaining insight into the etiopathogenesis of this form of muscle wasting. Furthermore, our demonstration that GHS administration efficaciously prevents cisplatin‐induced calcium homeostasis alteration contributes to elucidate the mechanism of action through which GHS could potentially ameliorate chemotherapy‐associated cachexia.